Ruhani communication: revealing conscience-based prophetic values in Jam’iyyatul Islamiyah, Indonesia - Syahputra, Iswandi; Riyanto, Waryani Fajar (Indonesian Journal of Islam and Muslim Societies, 2025)
This article presents a novel concept of ruhani communication, grounded in prophetic values, within the context of inner communication. Research data were collected through in-depth interviews with three key informants from Jam’iyyatul Islamiyah in Indonesia. The current study found that ruhani constitutes a spiritual aspect that functions as a communication partner within oneself. Ruhani possesses the prophetic features of shiddiq (righteousness), amanah (trust), tabligh (communicative), and fathanah (smart and wise). Ruhani, thus, exists within the spiritual plane. Yet, biologically, ruhani, which has the capacity to feel and record (Kitab), lies within the heart of every living human being. Hence, it is known as the voice of the heart or conscience. Ruhani, with the capacity to feel and record, which possesses prophetic values residing within the conscience, is the essence of the principal source in inner communication. Accordingly, the findings in this research will have implications for the currently established study of intrapersonal communication, leading towards a more essential and reflective innerpersonal communication. Artikel ini menawarkan gagasan baru tentang komunikasi ruhani yang berbasis nilai-nilai kenabian dalam konteks komunikasi batin. Data penelitian diperoleh dari wawancara mendalam terhadap tiga narasumber kunci di Jam’iyyatul Islamiyah, Indonesia. Penelitian ini menemukan ruhani sebagai pihak yang secara batiniah (spiritual) menjadi mitra komunikasi dalam diri setiap orang. Ruhani memiliki sifat kenabian, yaitu shiddiq (benar), amanah (dapat dipercaya), tabligh (menyampaikan), dan fathanah (cerdas dan bijaksana). Karena itu, ruhani berada dalam wilayah spiritual. Namun secara biologis, ruhani yang mampu merasa dan mencatat tersebut bersemayam di dalam hati setiap manusia yang hidup. Sehingga disebut sebagai suara hati nurani. Ruhani yang bisa merasa, mencatat (Kitab), dan memiliki sifat kenabian yang bersemayam di hati nurani inilah esensi dari sumber penting dalam komunikasi batin. Sehingga temuan penelitian ini akan berimplikasi pada kajian komunikasi intrapersonal yang sudah mapan saat ini, menjadi innerpersonal yang lebih esensial dan reflektif.